A scaled boundary finite element method model for interlaminar failure in composite laminates. (1st June 2020) - Dölling, S.; Hahn, J.; Felger, J.; Bremm, S.; Becker, W.
Abstract: Triggered by highly localized stress concentrations, failure of layered fibre-reinforced composites may occur in the form of an interface crack emanating from the laminate's free edges. In the present work, this so-called free-edge effect is examined using a scaled boundary finite element method (SBFEM) combined with a coupled stress and energy failure criterion. Focusing on symmetric angle-ply laminates, the SBFEM is formulated for a generalised plane strain state. This allows for a computationally efficient calculation of interface stresses as well as energy dissipation due to delamination of individual plies. For validation purposes, the SBFEM results are compared to analytical reference solutions based on the method of complex potentials. The effective longitudinal stress at failure is determined by means of the coupled stress and energy criterion. The effect of interface strength and toughness as well as the ply-thickness on the laminate's failure stress are discussed in detail. Predictions are validated against experimental findings from literature for different laminate types and layups.